Factors that contribute to persistent Listeria in food processing facilities and relevant interventions: A rapid review. (March 2022) - Belias, Alexandra; Sullivan, Genevieve; Wiedmann, Martin; Ivanek, Renata
Abstract: Persistent Listeria in food processing facilities is defined as Listeria that survives over time, even after cleaning and sanitation activities have been performed. Once persistence has established, it can be difficult to eliminate the Listeria . A rapid review was conducted to identify locations of persistent Listeria, risk factors for persistent Listeria, and interventions that have been successful in eliminating persistent Listeria in food processing environments. A systematic search was performed in Food Science and Technology Abstracts in the Web of Science database to identify studies; of the 1, 656 identified studies, 32 met the inclusion criteria. These 32 studies were conducted in seafood or smoked seafood processing facilities (n = 12), meat or poultry slaughter or processing facilities (n = 10), cheese processing facilities (n = 4), sandwich or deli meat processing facilities (n = 2), a produce facility (n = 1), and un-specified facilities or facilities that processed multiple product types (n = 3). This indicates there is a need for additional studies specific to produce. Of the 32 studies, only 13 included a definition of persistence; however, the definition of persistence was highly variable from study to study, suggesting a need to standardize the definition for Listeria persistence. Floors, drains, conveyor belts, slicers, and tables were the 5 most frequently mentioned sites where persistent Listeria was isolated in the included studies. Only 9 studies that discussed risk factors for persistent Listeria ; the 2 most common risk factors mentioned were equipment cleanability and lack of hygienic zoning. Eleven studies tested interventions for the elimination of persistent Listeria . In addition to summarizing the existing knowledge on Listeria persistence in food processing facilities, this review also delineates additional research needs, such as studies on Listeria persistence in produce operations and studies that identify risk factors for persistence as well as successful intervention strategies (i.e., corrective actions to eliminate or reduce persistent Listeria ).